miRNA-451a and miRNA-125a Expression Levels in Ankylosing Spondylitis: Impact on Disease Diagnosis, Prognosis, and Outcomes - Dina Salem Fotoh; Rasha Ibrahim Noreldin; Mohamed Soliman Rizk; Maha Mohamed Elsabaawy; Heba Ahmed Esaily (Journal of Immunology Research)
Background. Early diagnosis of ankylosing spondylitis (AS) is yet not elucidated, with a potential diagnostic glance of microRNAs (miRNAs). Aim. Study the expression profile of miRNA-451a and miRNA-125a in AS patients and their impact on disease activity and prognosis. Methods. A cross-sectional study included 55 AS patients diagnosed according to modified New York criteria in 1984 with 55 matched healthy controls. History, clinical examination, and disease activity assessment with Bath ankylosing spondylitis disease activity index (BASDAI) were done. Full laboratory and radiological assessment along with expression profile of m iRNA-451a and miRNA-125a were tabulated and analyzed. Results. Higher expression levels of miRNA-125a and lower of miRNA-451a in AS patients compared to controls. Furthermore, miRNA-125a expression was high in active AS patients compared to inactive patients and controls (7.0±3.4 vs. 4.1±2.1 vs. 2.6±0.6, p<0.001, respectively). miRNA-451a was significantly lower in active AS patients compared to inactive patients and controls (2.2±1.1 vs. 4.1±2.3 vs. 7.1±4.5, respectively). Both miRNAs (miRNA-125a and miRNA-451a) had evident accuracy for AS diagnosis with areas under the curve (AUC) of 0.788 and 0.802, respectively. miRNA-125a had potential impact on AS activity with AUC of 0.777. Plasma levels of both miRNAs were able to distinguish AS patients with structural damage with AUCs 0.775 and 0.692, respectively. Conclusions. Both miRNA-451a and miRNA-125a were found to be of great value as sensitive noninvasive diagnostic, prognostic, and disease burden biomarker of AS patients in Egypt with suggested further studies for future therapeutic implications.